STIGMATISASI DAN PROPAGANDA ANTI-SYIAH: SOROTAN DESKRIPTIF GERAKAN ANNAS - Ali Makhsum (CMES (Center of Middle Eastern Studies), 2019)
The term anti-Shi'a is prejudice or hatred towards Shiite Muslims based on their religion and heritage. Anti-Shi'a efforts portray Shia as dangerous teachings by linking the Iraq and Syria conflicts, thus forcing some religious groups and the Indonesian Ulema Council (MUI) to issue heretical fatwas for Shi'ite teachings. How does anti-Shi'a propaganda manifest in describing Shi'ism? This paper describes the plot and context of anti-Shi'a in Indonesia. The anti-Shi'a container known as the National Anti-Shi'a Alliance (ANNAS) has become a new medium in campaigning for Shiite heresy. The sentiment of this movement adds a new list of Islamic boxes by giving birth to exclusive Islam. The participation of extremist, Salafi and conservative groups in the Shia stigmatization resulted in sentiments and propaganda towards Shia teachings.